Self Regulated Learning, Self-Esteem, Dukungan Sosial dan Flow Akademik - Raida Daulah Amira; Abdul Muhid (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2020)
The purpose of this study was to determine the relationship between self regulated learning, self-esteem, social support with academic flow in students in the credits programs and regular programs. This research is a type of correlational quantitative research. In this research use the scale of self regulated learning, self-esteem scale, social support scale, and academic flow scale. The research subject compensated 85 from a total population of 890 through the population research and quota sampling. The method used in this study is a quantitative method with multiple analysis technique. The result showed the calculated F value = 38.874 with a significance of 0.000 < 0.05. This shows that the relationship of self regulated learning, self-esteem, social support together with academic flow among students in the credit program and reguler program, there is a significant relationship. So the proposed hypothesis is accepted, meaning that the self regulated learning, self-esteem, and social support they have, the higher the academic flow.